The burden of care among caregivers: a comparison between home care and palliative care - Yasemin Kurtoğlu (SERNEV, 2023)
Introduction: We aimed to determine whether there is a difference in care burden, anxiety, and depression between caregivers of patients living at home and those in the palliative care unit.Methods: The study was cross-sectional in the palliative care and home health units. The study population consisted of 1,879 patients. Different from home care, caregivers in the palliative unit were educated by the nurses on patient care during their stay in the hospital. A total of 186 caregivers were enrolled in the study. Unlike those receiving home care, caregivers of the patients in the palliative care unit received training on patient care while they were in the hospital. The care burden, anxiety, and depression levels of the caregivers in both groups were measured using the Zarit Caregiver Burden and Hospital Anxiety and Depression scales.Results: The mean age of the participants was 51.44±12.11 years. The caregivers' mean burden and anxiety scores were higher in palliative care compared to the homecare group. Both burden and anxiety scores were significantly higher in the palliative care group (p lt;0.001 and p =0.031, respectively).Conclusion: One of the distinguishing features of patients in the palliative care unit is the opportunity to provide ongoing medical support, social support, and education to the caregivers. However, the interventions at the palliative unit were not enough to compensate for the difference in the burden of care between the two groups.